2018
DOI: 10.1037/rel0000130
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the bucket list: Identity-centered religious calling, being, and action among parents.

Abstract: From a positive family psychology perspective, this study explores identity-centered religious calling, being, and action among parents of youth, that is, what religious parents believe they are called to be and to do in relation to their adolescent children. Twenty-nine Christian, Jewish, and Muslim families of youth (N ϭ 58 participants) were asked what they considered most important for them "to be" and "to do" as parents of faith. Qualitative analyses were conducted to determine major themes of responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…At the foundation of our qualitative method lies the analytic of open coding, the process of examining, comparing, conceptualizing, and categorizing data, as forwarded by Strauss and Corbin (1990) in grounded theory methodology. Additionally, we employ a qualitative, narrative-focused approach (i.e., Josselson & Lieblich, 1993)—an approach that has been recommended as an excellent fit with exploring meanings (whys) and processes (hows) at the sensitive nexus of religious faith and family relationships (Davis et al, 2016; Dollahite, Marks, Kear, Lewis, & Stokes, 2018). Indeed, narratives often help portray what is meaningful to participants, as well as why and how meaning has been derived or created.…”
Section: Methodsmentioning
confidence: 99%
“…At the foundation of our qualitative method lies the analytic of open coding, the process of examining, comparing, conceptualizing, and categorizing data, as forwarded by Strauss and Corbin (1990) in grounded theory methodology. Additionally, we employ a qualitative, narrative-focused approach (i.e., Josselson & Lieblich, 1993)—an approach that has been recommended as an excellent fit with exploring meanings (whys) and processes (hows) at the sensitive nexus of religious faith and family relationships (Davis et al, 2016; Dollahite, Marks, Kear, Lewis, & Stokes, 2018). Indeed, narratives often help portray what is meaningful to participants, as well as why and how meaning has been derived or created.…”
Section: Methodsmentioning
confidence: 99%
“…Religiosity is among the most potent personal and social forces at work in human experience and we believe it is also important to explore how to best employ and apply it for the benefit of individuals, couples, families, and society (Burr et al, 2012;Stark, 2012). Scholars may have collectively arrived at a point in the evolution of the social and behavioral sciences, religious studies, and human communications that we can formulate and disseminate a set of principles and processes that will allow us to help a large proportion of human beings to live at the nexus of faith and family life in optimal and authentic ways for persons (children, youth, adults) and relationships (see Dollahite, Marks, Kear, Lewis, & Stokes, 2017). We believe that understanding how to harness the positive power of dualities while more carefully navigating negative and damaging approaches to dualities can be a vitally important asset for families and professionals striving to help them.…”
Section: Saving Faith: Harnessing the Power Of Duality For Goodmentioning
confidence: 99%
“…(Chaney, Marks, Sasser, & Hopkins, ; Dollahite, Layton, Bahr, Walker, & Thatcher, ; Dollahite, Marks, Kear, Lewis, & Stokes, ; Dollahite & Thatcher, ; Layton, Dollahite, & Hardy, ; Layton, Hardy, & Dollahite, ). Participants reported that their religious beliefs sanctified parent–child connections, elevating them to a sacred nature (see Mahoney, Pargament, Murray‐Swank, & Murray‐Swank, ).…”
Section: Generative Devotion Frameworkmentioning
confidence: 99%